Determining the prevalence of musculoskeletal injuries and its relationship with workplace posture in copper industry repairmen - Masuomeh KARAMI; Saeid GHANE EZABADI; Zohreh KARAMI; Yaser SAHRANAVARD (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Introduction: Musculoskeletal disorders are one of the most common causes of occupational injuries that mainly affect the low back, neck, and upper limbs. Preventing these discomforts requires assessing workplace posture using ergonomic job analysis methods. The aim of this study was to determine the rate of musculoskeletal injuries of mechanical repairs using REBA method in 2018 in Sarcheshmeh copper mine. Methods: In this descriptive-analytical study, the workplace posture of 65 mechanical repairs were evaluated using REBA method. The prevalence of musculoskeletal disorders was also obtained using the Nordic questionnaire. The collected data were analyzed by SPSS 20. Results: In this study, the prevalence of wrist discomfort was 43.07%, neck 18.46%, shoulder 33.84%, low back 53.85%, and leg 27.70%. Regarding the risk level of the right limb, 9.25% of the subjects were at a low level, 46.15% at a medium level, 32.30% at a high level, and 12.30% at a very high level. Also, regarding the risk level of the left limb, 4.62% of the subjects were at a low level, 64.61% at a medium level, 26.15% at a high level, and 4.62% at a very high level. Conclusion: These results indicated that the workplace posture of the subjects needed to be improved. To prevent the occurrence of these disorders, education is required to recognize biomechanical risk factors and correct methods of working, use of appropriate tools and appropriate to the work process, and improvement and control of stressors and environmental factors.